Economic Life in the Islamic City during the Mamluk Era in Egypt, Syria, and Palestine (1250-1517): Feudalism, Economic Policies, and the Monetary Inflation Crisis - Al-Chikh Ali, Samir Hassan (Journal of Humanities & Social Sciences, 2025)
This study investigates the economic life in Islamic cities during the Mamluk era in Egypt, Syria, and Palestine (1250-1517 AD), focusing on the military feudal system, economic policies, and the monetary inflation crisis. The research employs a descriptive historical approach and socio-economic analysis of statistical data. Findings reveal that the military feudal system led to economic monopolization by the ruling elite, with cities shifting towards an export economy targeting European markets, especially Italy. The influx of European gold and silver currencies mixed with copper caused a monetary inflation crisis, negatively impacting purchasing power and urban markets. Customs policies reduced tariffs on European imports while raising them on local exports, devastating local industries and causing a decline in industrial and commercial production. These economic and political factors contributed to the disintegration and fall of the Mamluk regime. The study recommends further research on the role of cities like Aleppo and Alexandria in Levantine trade, the causes of monetary inflation, and the impact of precious metals from the New World on European and Middle Eastern markets.
Keywords: Economic life; Islamic cities; Mamluk era; military feudalism; monetary inflation; economic policies